CAPITALIZATION RATE, INTERNALLY GENERATED INTANGIBLE ASSETS, AND THE VALUE RELEVANCE OF ACCOUNTING INFORMATION: EVIDENCE FROM INDONESIA - Widyatama W.W. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
The purpose of this study is to examine the effect of internally generated intangible assets’ capitalization rate at the firm level on the value relevance of accounting information. Capitalization rate is defined as the tendency of a firm to capitalize their expenditures that may have future benefit for the firm. In accordance with the matching concept, expenditures that may have future benefit for the firm should be capitalized to provide more accurate information to investors related to the financial performance of the firm. Thus, it is hypothesized in this study that a greater capitalization rate for the internally generated intangible asset improves the value relevance of accounting information. Timeliness of publication and negative earnings presence were included as the controlling variables. 31 firms were selected through the purposive sampling method. The data collected are secondary data and the data analysis technique utilized was the multilple linear regression analysis. However, the analysis results showed that capitalization rate does not have a significant effect on the value relevance of accounting information with timeliness and negative earnings presence as the controlling variables. After the inclusion of firms that do not use Indonesian Rupiah as their reporting currency, the total sample only increased by 2, with a total of 33 firms. Despite this inclusion, the hypothesis was still rejected. The data also shows that most firms provide inadequate information regarding their intangible assets.